The Effect of Combination Psophocarpus Tetragonolobus and Pisum sativum Extract on The Histological Structure of The Liver, Kidney and Stomach of Rattus norvegicus - Triharjana; Elfidariani, Ratih (Indonesian Journal of Bioscience (IJOBI), 2023)
This research aim to determine the effect of the extract of winged bean (Psophocarpus tetragonolobus) and peas (Pisum sativum) toward histological structure of the liver, kidneys, and stomach of white rats (Rattus norvegicus). The objects of this research are twenty (20) white rats female wistar strain with ±100-200 grams of weigh which had never been pregnant. White rat samples are divided into 1 group as a control (P0) and 3 treatment groups with P1 25 mg/kgBB of winged bean extract + 75 mg / kgBB of peas extract, P2 50 mg / kgBB of winged bean extract + peas extract 50 mg / kgBB, and P3 winged bean extract 75 mg / kgBB + peas extract 25 mg / kgBB given for 21 days. Each group consist of 5 repetitions. The analysis used the One Way Anova test, it the results were significant, and then proceed with the Duncan's Multiple Range Test (DMRT) test. To determine the trend of the effect of winged bean seed extract and pea on the histological structure of the liver, kidneys, and stomach, descriptive analysis was performed. The results showed that the extract of winged bean and pea had no significant effect (p> 0.05) on the histological structural damage of the liver and kidneys of white rats. Giving winged bean extract) and peas extract on the histological structure of the stomach of white rats in all treatment groups was under normal conditions.